Indigenous Storytelling as Decolonial Praxis: Reclaiming Voice and Land in Ben Okri’s The Famished Road - Agyo, Azetu Azashi; Aguiyi, Joy Ogechi (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
This research explores the pivotal role of indigenous storytelling as a decolonial strategy in Ben Okri’s The Famished Road. Drawing on postcolonial theory as articulated by Frantz Fanon, Aimé Césaire, Edward Said, and contemporary critics such as Ashcroft, Griffiths, and Tiffin, the study situates Okri’s novel within the broader context of Africa’s ongoing struggle to reclaim voice, land, and cultural identity in the aftermath of colonialism. The analysis foregrounds how Okri employs Yoruba cosmology, oral narrative forms, and mythic structures to resist colonial epistemologies and assert indigenous worldviews. By engaging with the works of scholars like Marnta Rani, Nasta Shushella, Simon Gikandi, and Ato Quayson, the research demonstrates that storytelling in The Famished Road is not merely a literary device but a dynamic force for cultural survival, resistance, and renewal. Through close textual analysis and critical engagement with historical and theoretical sources, the study reveals how Okri’s narrative practices challenge neocolonial power structures, amplify marginalized voices, and contribute to the ongoing project of decolonization in African literature.